Boredom in Adolescence: Validation of the Italian Version of the Multidimensional State Boredom Scale (MSBS) in Adolescents - Andrea Spoto; Sara Iannattone; Perla Valentini; Alessia Raffagnato; Marina Miscioscia; Michela Gatta (MDPI AG, 2021)
Boredom in adolescence is often underestimated, although it may be the sign of a profound unease or be associated with psychological disorders. Given the complexity of the construct of boredom and its increasing prevalence among adolescents in recent years, the present study aimed to validate the factorial structure of the Italian version of the Multidimensional State Boredom Scale (MSBS) in adolescents using a cross-validation approach. The study involved 272 students (33.8% males, 66.2% females) aged 14-19 (M = 15.9, SD = 1.38) living in northern and central Italy. In addition to the MSBS, the Symptoms Checklist 90-R (SCL 90-R) and the Children's Depression Inventory (CDI) were administered. Exploratory and confirmatory factor analyses validated a 23-item structure of the MSBS, comprising five correlated factors. The tool showed a good internal consistency for these factors and a good convergent and factor validity. The MSBS consequently seems a valid and reliable method for assessing boredom in adolescence. The cut-off for the total score that could pinpoint cases posing a potential clinical risk was 88. A weak correlation was found between the total level of boredom and the daily Internet usage, while no relationship emerged between boredom and age, gender, and grades. Since excessive levels of boredom may conceal a general unease that could develop into structured psychological disorders, the value of the MSBS lies in enabling us to identify in advance adolescents at potential clinical risk.